HUBUNGAN POLIMORFISME GEN SCN1A DENGAN RESPONS TERHADAP OBAT ANTI EPILEPSI FENITOIN DAN KARBAMAZEPIN - Ardefiyenti, Basjiruddin A, Jamsari MP (Neurona Majalah Kedokteran Neuro Sains, 2012)
INTRODUCTION PHENYTOIN AND CARBAMAZEPINE ARE THE FIRST LINE AED ANTIEPILEPTIC DRUG THAT ARE WIDELY USED IN THE TREATMENT OF EPILEPSY PHENYTOIN AND CARBAMAZEPINE WORKS BY BLOCKING SODIUM CHANNELS SCN1A GENE IS A GENE THAT CODES THE FORMATION OF THE SODIUM CHANNEL THE PRESENCE OF FUNCTIONAL POLYMORPHISMS WILL CAUSE DISRUPTION TO THE SODIUM CANAL CAUSING AED DOES NOT WORK TO OVERCOME SEIZURES THIS STUDY PURPOSED TO DETERMINE THE TYPE OF SCN1A GENE POLYMORPHISM AND RESPONSE TO AED